The complete chloroplast genome of Douinia plicata (Lindb.) Konstant. & Vilnet (Scapaniaceae, Jungermanniales) - Bum, Hyun Min (Mitochondrial DNA B Resour, 2020)
We completed chloroplast genome of Douinia plicata (Lindb.) Konstant. & Vilnet., presenting morphological features including denticulate leaf margin, verrucose cuticle on base of leaves, and 80–100° keel angle with stem at the midleaf. It is 118,797 bp long (GC ratio is 33.9%) and has four subregions: 81,142 bp of large single copy (31.9%) and 19,611 bp of small single copy (31.0%) regions are separated by 9,017 bp of inverted repeat (46.3%) regions including 130 genes (86 protein-coding genes, eight rRNAs, and 36 tRNAs). Phylogenetic trees show D. plicata is clustered with two Scapania species.